Tremendous Changes in India after Paris Climate Change Conference - Bantu, Tirupati rao; Adapa, Sattibabu; Veeravalli, Suryanarayana (International Journal of Scientific Research and Management (IJSRM), 2017)
India is the first Nation in the Earth to have made provisions for the conservation, preservation andprotection of environment in its constitution .On 5th June 1972 environment was first discussed as an itemof U.N Conference on human environment development in Stockholm and thereafter our country tooklegislative steps for environmental protection. The Paris Climate Change Conference was successfullyconcluded with the Paris Agreement, which is a Turning Point for the world in Inclusively Oppose climatechange. By Engage in IPCC (Intergovernmental panel on climate change) assessments, adopting newmethods and conducting national climate change assessments, India has been increasing its understandingof the issue. Moreover, this participation indicates India‘s dedication to including climate changes in itsecological balance program, sustainable development and conducts a low-carbon Group and Affluence.The constructive involvement in global governance shows that India is a responsible power to bothdeveloped and under developing nations.